CALCULATION OF CHEMICAL EQUILIBRIUM IN THE INTERSTELLAR CLOUD - Shmeld, I.; Freimanis, J.; Bochkarev, N. G. (Одеські астрономічні публікації, 2017)
In order to calculate the molecular concentrations in the interstellar cloud and to obtain heir spatial distribution we have made a computational code to solve the set of equations for chemical equilibrium and equations of charge and atom balance. Now 109 molecules and 1070 chemical reactions are included. Besides, the gas phase reactions with neutrals and ions, formation of molecular hydrogen on grains and the ionization and dissociation due to cosmic rays and UV radiation were taken into account. In order to calculate the photodissociation rates of H2 and CO molecules we take into consideration: i) extinction due to H2 Lyman and Werner series bands, ii) extinction due to atomic H Lyman series lines - up to n=1 -> n=51, iii) extinction due to 33 CO bands and dust continuum extinction. Only UV continuum for photodissociation of all other species was taken into account.